Aktualisasi Pemberdayaan SDM Pelaku UMKM Kembulsari Melalui Pemberian Motivasi Dan Pendampingan Foto Produk (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
This activity aims to increase motivation and product photography skills among Kembulsari MSMEs. The Covid-19 pandemic has had a tremendous impact on MSMEs. The physical distance that was implemented at that time caused the sales turnover level of MSMEs to decline to the point that many entrepreneurs stopped production. The pandemic has caused weaknesses in Kembulsari MSMEs and their business continuity. To rebuild the enthusiasm of MSME players in running their businesses, an injection of motivation is needed. Motivation becomes a support system for the basis of self-development intentions. On the other hand, physical distancing means that digital transformation in the marketing sector must be carried out to increase sales volume. These two core problems are the focus of providing solutions for community service activities. Activities carried out offline include initial studies to map problems, coordination with the team and MSME actors, actualization of activities, then regular monitoring. The methods used are lectures, tutorials and discussions. The results of these activities are increased responsibility, work performance and recognition of work performance, MSME players have attractive product photos and increased sales volume. This empowerment succeeded in providing motivation and improving MSME product photography skills